Patterns of nutrients distribution along salinity gradient in the estuaries of the rivers Sukhodol and Razdolnaya/Suifen (Peter the Great Bay, Japan Sea) - Anna S. Vazhova; Yury I. Zuenko (Известия ТИНРО)
Sign of production-destruction balance is determined for different parts of two rivers estuaries in Peter the Great Bay (Razdolnaya/Suifen and Sukhodol) on the data of chemical samplings in different seasons of 2010-2013. For this purpose, the nutrients concentration dependence on ratio of river and sea waters mixing is determined. In the case of conservative behavior of nutrients, their concentration should have negative linear dependence on increasing salinity, but its non-linearity shows removal or addition of the nutrients by processes of biological production or destruction: negative deviations indicate production and positive deviations indicate destruction. The concentration of mineral nitrogen is close to zero everywhere in the estuaries in spring, so below the line of conservative behavior that is the evidence of active nitrogen consumption. Patterns of silicon and phosphorus distribution are similar to the distribution of nitrogen. Summer nutrients concentrations are mainly below the conservative values, as well, with exception of the areas at the river bar, so production prevails in the external estuaries of both rivers, but remineralization prevails in the lower parts of the internal estuaries in this season. In autumn, destruction of organic matter becomes more important in both estuaries, so heightened values of nutrients are observed in all their parts, in particular in the «silicon belt» of brackish water (≈ 13-17 eps). The silicon concentration increasing at the river bar (above the concentration in the river water) is the most significant in the Razdolnaya estuary which is generally poor by this nutrient. There is concluded that terrigenous nutrients of the river water are utilized for new production mostly in the external estuaries, whereas the process of organic matter mineralization dominates in the internal estuaries. Besides of the production-destruction processes, changes of the mineral silicon concentration are determined by transformation of its inorganic forms, as dissociation of low-soluble silicates to silicon acid under heightened pH. Principal difference of the production-destruction balance between the internal and external parts of estuary could be an ecological basis for formation of different ecosystems in these zones, with principally different structure and functioning patterns.